Pujian dan kritikan terhadap Imam Al-Ghazali - Abdul Salam Hj. Yussof (Universiti Kebangsaan Malaysia, 2005)
Born in eastern Iran, Abu Hamid al-Ghazali was known as Islam’s most gifted scholar. He taught law in Baghdad, but in 1095 resigned and for 12 years wandered the desert as a Sufi mystic. Al-Ghazali is considered the most influential Islamic philosopher of the medieval period, known for reviving mysticism and critiquing rationalism within orthodox Islam. In 1106 he returned to teaching, the most renowned Islamic theologian of his time. His most famous books are Tuhafat al-Falasifa (The Incoherence of the Philosophers) and Ihya al-’Ulum al-Islamia (The Revival of the Religious Sciences). Al-Ghazālī has contributed a lot in the area studied and is the most distinguished thinkers in the development of knowledge in his era. Until today, his work is still being referred to in facing the challenges of contemporary era. The ideas in the area studied never stop expanding day by day